2019
DOI: 10.3389/fspas.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnetic Field in Molecular Cloud Formation and Evolution

Abstract: We review the role that magnetic field may have on the formation and evolution of molecular clouds. After a brief presentation and main assumptions leading to ideal MHD equations, their most important correction, namely the ion-neutral drift is described. The nature of the multi-phase interstellar medium (ISM) and the thermal processes that allows this gas to become denser are presented. Then we discuss our current knowledge of compressible magnetized turbulence, thought to play a fundamental role in the ISM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
124
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(127 citation statements)
references
References 251 publications
(400 reference statements)
1
124
1
Order By: Relevance
“…One of the major outcome of the first calculations of magnetized collapse (e.g. Allen et al 2003;Galli et al 2006;Price & Bate 2007;Hennebelle & Fromang 2008;Li et al 2014;Wurster & Li 2018;Hennebelle & Inutsuka 2019), is that magnetic braking could be so efficient that disc formation may be entirely prevented, a process named as catastrophic braking. Further studies have shown that the aligned configuration assumed in these calculations was however a significant oversimplification and that discs should form in magnetized clouds, although the discs are smaller in size and fragment less than in the absence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major outcome of the first calculations of magnetized collapse (e.g. Allen et al 2003;Galli et al 2006;Price & Bate 2007;Hennebelle & Fromang 2008;Li et al 2014;Wurster & Li 2018;Hennebelle & Inutsuka 2019), is that magnetic braking could be so efficient that disc formation may be entirely prevented, a process named as catastrophic braking. Further studies have shown that the aligned configuration assumed in these calculations was however a significant oversimplification and that discs should form in magnetized clouds, although the discs are smaller in size and fragment less than in the absence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic fields are known to play a critical role in many aspects of both low-and high-mass star formation. Even weakly ionized star-forming material is coupled to the ambient magnetic field, and thus the field can regulate (or prevent) the collapse and fragmentation of star-forming clouds (Hennebelle and Inutsuka, 2019;Krumholz and Federrath, 2019;Teyssier and Commerçon, 2019, in this volume), can influence the formation of protoplanetary disks (Wurster and Li, 2018, in this volume), and can launch bipolar outflows and jets from young protostars (Pudritz and Ray, 2019, in this volume). Mapping the morphology of magnetic fields in low-and high-mass star-forming regions is therefore critical to better understand how magnetic fields affect the star-formation process at early times, and how the role of the field changes relative to other dynamical effects (e.g., turbulence, rotation, thermal and radiation pressure, and gravitational collapse) as a function of spatial scale, source environment, and source mass.…”
Section: Introductionmentioning
confidence: 99%
“…Observations indicate that in flux-freezing conditions, the interstellar magnetic fields, gas pressure, cosmic-ray pressure, and gravity are the most important forces on the diffuse gas (Heiles & Crutcher 2005). It is likely that magnetic fields are responsible for reducing the star formation rate in dense molecular clouds (MCs) by a factor of a few by strongly shaping the interstellar gas (Hennebelle & Inutsuka 2019, and references therein). However, observing the magnetic fields in and around MCs and determining their exact influence is a difficult task.…”
Section: Introductionmentioning
confidence: 99%